PENERAPAN PEMBELAJARAN DARING MELALUI PLATFORM BELAJAR SMARTIFY TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI SISTEM PENCERNAAN - Yudittianti Rizki Tania Firdausy; An Nuril Maulida Fauziyah (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This research aims to describe the improvement of learning outcomes and responses of junior high school students to Smartify learning media on the digestive system material. The research design used the One-Group Pretest-Posttest Design. The research subjects used were students of class VIII-A of SMPN 1 Sumberrejo, Bojonegoro Regency, with a total of 26 students. This research used a test sheet and a questionnaire. The results of data collection were analyzed using the average value to measure the implementation of learning, calculate the Normalized Gain (N-Gain) test to determine the category of improving pretest and posttest results and calculate the percentage in each question to measure student responses. In this research, the results of the Normalized Gain test obtained by the students showed that 87% of students scored in the high category and showed that there was an increase between the results of the pretest and posttest. Student response of 57% of students gave a score of 4 to the platform Smartify in other words they agreed that the platform Smartify could be used as an alternative to online learning and could improve learning outcomes. A total of 43% of them gave a score of 5 in other words they strongly agree regarding the platform Smartify which can be used as an alternative to online learning and can improve learning outcomes. The conclusion of this research is that the implementation of online learning through the platform Smartify can improve student learning outcomes on the digestive system material in class VIII-A students of SMP Negeri 1 Sumberrejo.